Pengembangan dan Evaluasi Sistem Informasi Penjualan Berbasis Web melalui Usability dan Efisiensi Operasional - Algikka Algikka; Kiswanto Kiswanto (STMIK Banjarbaru, 2026)
Previously, all sales transactions at Mahmud Racing Apparel were managed manually through social media, leading to difficulties in data tracking, high susceptibility to recording errors, and delays in compiling sales reports. To address these challenges, this research centers on the design and engineering of a digital data management platform utilizing the Rapid Application Development (RAD) approach, alongside functional verification and the System Usability Scale (SUS) framework. All planned testing cases were accomplished with zero average SUS score reached 82, which is classified as